A CROSS-SECTIONAL STUDY ON SELF MEDICATION PATTERN AMONG MEDICAL STUDENTS AT KANNUR, NORTH KERALA - Girish H.O; Divya H.M; Sarada Prabhakaran; Venugopalan P.P; Raghavendraswamy Koppad; Abhishek Acharya (Journal of Evolution of M edical and Dental Sciences, 2013)
BACKGROUND: Self medication is mainly symptomatic based and may lead to the masking of signs and symptoms of underlying disease. Medical students being exposed to the subjects in medicine are more prone for self medication. This raises the concerns of incorrect self- diagnosis, drug interaction, and use of drugs other than for the original indication. AIMS: To study the pattern of self medication among medical students and to determine the factors affecting it. METHODS AND MATERIAL: STUDY DESIGN & SETTING: A cross-sectional descriptive study done in a medical college. Study Duration: March 15 th to April 20 th 2013. Participants: Out of 400 students, 302 students who were willing to participate and available during study period were enrolled in the study. Representation from all phases/batches of MBBS course was ensured, accounting to 77, 84, 63 and 78 students from first, second, third and final phase of MBBS. Data collection: By self administered pre-tested & validated questionnaire. Statistical analysis was done by applying proportions/percentages. RESULTS: Out of 302 participants, 25.8% were males & 74.2% were females. Practice of self medication was reported by 64.9% students. It was 16.9% in first phase students which shoot to 100% in final phase. Practice of self medication was higher in males while the frequency of self medication was higher in females. Seniors (89.8%) and previous prescriptions (87.2%) were the most common sources for reference. Fever (70.4%), common cold (67.8%) and headache/bodyache (64.7%) were the common reasons for self medication. Analgesics (79.6%), antipyretics (79.6%) and anti-histaminic (72.4%) were the most common drugs used for self medication. 30.1% of them took antibiotics and 9.7% sedatives without prescription. 80.1% (157) of those who took self medication said that they prescribed drugs for others also (friends/relatives). None of them suffered any adverse effects. CONCLUSIONS: The practice of self medication is widely prevalent in medical students especially among third and final phase students. This may possibly mask the initial signs and symptoms of diseases and lead to making a wrong diagnosis and risk of using a wrong drug. This highlights the importance of impressing the students about the dangers of self medication, their misuse and their responsibility.